Pengaruh Digital Marketing dan Brand Image terhadap Keputusan Pembelian dengan Trust sebagai Variabel Moderasi pada Produk Brownies Cinta di Karanganyar: Survey pada Konsumen Produk Brownies Cinta Karanganyar - Aditya Indah Wulandari; Rahmasita Pramudya Yudhiarti; Aditya Firdaus Al-Husain; Pria Andhika; Marjam Desma Rahadhini (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The study's foundation is the swift growth of the snack food sector with an emphasis on brownies, particularly the Brownies Cinta MSME in Karanganyar, which struggles to manage digital tactics and cultivate a brand identity to expand consumer choice. With trust acting as a moderating variable, the goal of this study is to investigate how brand image and digital marketing affect consumer decisions. Using a quantitative approach, 33 respondents participated in multiple linear regression analysis and moderated regression analysis (MRA). SPSS Statistic Version 25 software was used for statistical testing. The results of the study demonstrated that, although digital marketing had no discernible effect on purchasing decisions, brand image did. Furthermore, the association between digital marketing and brand image on purchase decisions was not effectively moderated by customer trust. The study's conclusions highlight how crucial MSMEs are to developing a strong brand image through consistent product quality and visual communication, as well as enhancing digital marketing tactics to better draw in customers and increase their interest in making a purchase. Additionally, this study demonstrates that consumer trust is still important even though it hasn't been statistically demonstrated to be a moderator. As a result, businesses must uphold their reputation and transparency in their digital interactions.